2018
DOI: 10.1016/j.conctc.2018.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Interventionist training and intervention fidelity monitoring and maintenance for CONNECT, a nurse-led primary palliative care in oncology trial

Abstract: ContextIntervention fidelity is a critical component of behavioral research that has received inadequate attention in palliative care studies. With increasing focus on the need for palliative care models that can be widely disseminated and delivered by non-specialists, rigorous yet pragmatic strategies for training interventionists and maintaining intervention fidelity are needed.Objectives(1) Describe components of a plan for interventionist training and monitoring and maintaining intervention fidelity as par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…Therefore, the intervention was divided into several clear defined components. For all components the fidelty was over 80% [23]. The difference with our study may be caused by a different method for assessing intervention fidelity, by the focus on routine clinical practice, by differences in the situation at baseline, or by other differences.…”
Section: Discussionmentioning
confidence: 57%
“…Therefore, the intervention was divided into several clear defined components. For all components the fidelty was over 80% [23]. The difference with our study may be caused by a different method for assessing intervention fidelity, by the focus on routine clinical practice, by differences in the situation at baseline, or by other differences.…”
Section: Discussionmentioning
confidence: 57%
“…We found that in PROVEN’s high-adherence facilities, champions perceived that facilitation driven by the leadership team (i.e., ongoing qualitative feedback and coaching via conference calls) was beneficial. These leadership team-driven activities, promoted by other studies of palliative care interventions [3538], may have differentially enhanced participant responsiveness if high-adherence (versus low-adherence) facility champions self-selected into conference call participation. Indeed, investigators from the INTERACT trial and from a feasibility study of another long-term care-based ACP intervention revealed the influence of sharing successes with champions [33, 39].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the pivotal role of the Clinical Nurse Specialist requires further definition. This may contribute to research exploring the role of oncology nurses to help address symptom needs, coordinate care and offer advance care planning [41].…”
Section: Implications and Unanswered Questionsmentioning
confidence: 99%